An evaluation of the text book New English File Pre-intermediate" for the first year non-English majored students at University of Social Sciences and Humanities; suggestions for book use and adaptation - Dao, Thi Sang (University of Languages and International Studies, 2017)
There is no doubt that material evaluation is one of the essential components in the teaching and learning process of any languages. From this fact, the thesis was conducted to evaluate the material “New English File pre-intermediate” which is in current u (...)